Seed is key factor in onion production- Farmer’s feedback - A, Sable P; Patel, J R (Indian Horticulture, 2023)
Sh. Shyamalbhai Dhulabhai Patel, a farmer of village Matoda, Tal. Khedbrahma, Dist. Sabarkantha, Gujarat was transplanting rabi onion by purchasing locally available seedlings. He was unable to get satisfactory income because of higher seedling cost, bolting and doubling of bulbs per cent, mixture of different varieties bulbs thereby low yield. KVK scientists helped him to enhance bulb yield potential with quality and income than income generated from onion crop transplanted by purchasing locally available seedlings.